Critical Perspectives on Nursing’s Impact in Shaping Healthcare Outcomes - Alenizy, Seta Abdulrahman; Alanaz, Taghreed Hakeem; Alanazi, Manal Jubayr; Alotaibi, Manar Mohammed; Alanazi, Dalal Abdalrahman; Alshehri, Etra Mohammed; Alotaibi, Asma Munif; Aldossari, Modih Saud; Ali, Fatima Mohammed; Alanazi, Amal Fayadh; Majrashi, Ameera Ahmad (Journal of Ecohumanism, 2024)
Of critical importance is the function of nursing, which has a much broader responsibility than simply providing direct patient care for individuals or performing advocacy roles for patients and families. Nurses are crucial to elevating the impact of clinical results, decreasing hospital deinstitutionalization rates, advancing patient security, and optimizing healthcare organization performance. Despite their importance, difficulties, including staff deficits and the issue of professional independence, along with diverse standards of nursing all over the world, remain unresolved. This review will evaluate the nursing contribution to various healthcare results, challenges nurses face in various settings, and prospects of enhancing the results through leadership and nursing inputs. It cites many issues from the literature and presents patterns and suggestions for solidifying nursing in future healthcare systems.